Rate Adaptation for Avoiding Congestion in the Use of Multimedia Over User Datagram Protocol - Hamed, Wessam Abbas (2012)
Multimedia applications have increased rapidly in the Internet today. However, multimedia communication suffers from bandwidth requirements problem. Therefore, it is important to optimize the network bandwidth utilization. Optimizing the network bandwidth utilization allows increasing the number of users who use multimedia applications that require guaranteed quality of service. The user experiences the performance during using the network service, which is the important factor to determine the users’ satisfaction. With the limitation of the network bandwidth, multimedia traffic can cause congestion which degrades the performance experienced by the network users. Therefore, there is an essential need to reduce the occurrence of congestion situations in a network to optimize the utilization of network resources to provide the network users with suitable performance. For most of multimedia applications, UDP is used as transport protocol. Current UDP implementation helps in increasing the traffic as it does not have flow or congestion control mechanisms. Congestion can be avoided when the traffic arrival rate to a gateway maintained close to the outgoing link capacities and the gateways' queue lengths kept small to guarantee the availability of buffer capacity for successful buffering and consequent forwarding of temporary traffic upsurges which could otherwise cause buffer overflows and packet loss. Congestion management is the combined responsibility of network gateways and end-point hosts. Gateways are invested with the ability to delay or drop the packets inside the network. Gateways are responsible for congestion detection & notification delivery, queue's traffic arrival rate control, and queue length control. Traffic sources are responsible for the adjustment of their data transmission rates to enable the gateways to achieve their goals. Building a new responsive multimedia application and protocol, based on the UDP concept, can decrease the congestion occurrence and enhance the performance of the network, especially in the real-time environment.